Peningkatan Motivasi Belajar Bahasa Indonesia Melalui Metode Struktural Analitik Sintetik Pada Siswa Kelas I Semester Ii Sdn Tambaharjo 01 Pati Tahun 2014/2015 - Rahmawati, Kundiyah; , Drs. Suwarno, SH., M. Pd (2015)
The background of the study is the low acquisition student learning outcomes in subjects Indonesian. This is because the students do not understand the material presented in a lecture mode. In addition, teachers are less skilled in using a variety of strategies or a variety of learning methods. The purpose of this research is to improve students' motivation to learn Indonesian first class SDN Tambaharjo 01 District Pati. The subjects of this study were students of class I, amounting to 33 people (which consisted of 14 boys and 19 girls) and Elementary School first grade teacher Tambaharjo 01 District Pati, Pati regency. While the object of this research is the aspect of reading fluently. This research was conducted in several stages of the cycle. Each cycle of planning, implementation, observation and reflection. The interactive techniques to reduce the data used by the data obtained in the field, display the data, draw conclusions, and verification. Data collection methods used by the test method, interviews, documentation, observation. The results of research by applying the method of Structural Analytical Synthetic results are quite satisfactory. It can be shown from the average mastery of learning outcomes gained increasing. Pre initial learning or mastery learning cycle is the percentage of students 21%, Cycle I (1) the percentage of completeness of student learning outcomes 30%, Cycle I (2) the percentage of students learning mastery 64%, the second cycle of completeness percentage of student learning outcomes 85%. Thus, it can be said that the application of SAS method can increase the motivation to learn Indonesian first grade students of SDN Tambaharjo 01.